Islamic Values in Mathematics Education: A Bibliometric Analysis with Emphasis on Educational Management Trends - Hamdanah, Hamdanah; Crismono, Prima Cristi; Yakoh, Mahnawawe (JURNAL AL-TANZIM, 2025)
This study aims to analyze the integration of Islamic values in mathematics education through a bibliometric approach, with a focus on trends in educational management. The background of this research lies in the growing attention to value education within the context of holistic education, alongside the lack of systematic mapping regarding the relationship among the concepts of "Islamic", "Mathematics", and "Education." Utilizing VOSviewer software, bibliographic data from scientific publications over the past ten years were analyzed to identify keyword networks, thematic trends, and the intensity of author contributions. The visualization results indicate that mathematics education serves as a central node, closely connected to Islamic values, student-centered learning, and blended learning, signaling a strong integration of spiritual values with modern learning approaches. Moreover, the linkages with STEM and science education demonstrate that Islamic value-based education is highly compatible with the direction of globalized education. The heatmap visualization also reveals authors' contributions to key themes, showing a balanced tendency between specialization and generalization. This study concludes that the development of holistic mathematics education management must integrate cognitive, affective, and spiritual aspects cohesively, while promoting contextual, adaptive, and value-based policies and curricula.